Development of SCP-SQ-SCS Based Student Worksheets flat building materials for elementary school teacher education students - Hadaming , Hamdana; Muhammad Arif Tiro; Hamzah Upu (International Journal of Technology and Education Research, 2025)
This research was conducted with the aim of producing an SCP-SQ-SCS (Stimulation, Concept Understanding, Problem, Search, Question, Solve, Create, and Share) based Student Worksheet in improving mathematical critical thinking skills that meet valid, practical, and effective criteria that can be applied in mathematics lectures for PGSD students. The model development process refers to the development model according to Nieveen, which includes (1) a preliminary stage. This phase involves finding that lecturers need an SCP-SQ-SCS-based Student Worksheet that trains students' critical thinking skills, which contains tasks that can develop students' critical thinking skills. (2) prototyping stage. This phase is designed as an SCP-SQ-SCS-based Student Worksheet, which includes the learning syntax of the SCP-SQ-SCS model. In addition to the validity of WORKSHEETs, the student response questionnaires, student activity observation sheets, and learning implementation observation sheets are also in the very valid category. (3) assessment stage. At this stage, the practicality and effectiveness of the SCP-SQ-SCS-based student worksheet were established. The practicality of the lecturer's response questionnaire analysis results showed a positive response to the Student Worksheet used. The results of the data analysis from the lecturer response questionnaire indicated that the average percentage of lecturer responses, at 92%, fell into the very positive category. The effectiveness of SCP-SQ-SCS-BASED Student Worksheets is seen from the results of data analysis of the components of student activity effectiveness; student response; and learning outcome tests, namely (1) the average percentage of student activities in the implementation of SCP-SQ-SCS-BASED Student WorksheetsIt is at the "good" criteria (2) the average percentage of student responses gives a positive response, and (3) the classical complete learning outcome test.